2006
DOI: 10.1080/15438620600985829
|View full text |Cite
|
Sign up to set email alerts
|

Upper Body Contribution During Leg Cycling Peak Power in Teenage Boys and Girls

Abstract: This study investigated gender differences in upper-body contribution to cycle muscle power in 23 adolescents. All subjects performed two 5-s and one 20-s cycling sprint, using two protocols: with handgrip (WG) and without handgrip (WOG). Maximal handgrip strength was assessed for each individual. Absolute peak and mean cycling power was corrected for total fat-free mass (FFM) and for lean leg volume (LLV). Males showed higher cycling performance than females. Peak power and 20-s mean power (flywheel inertia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
(30 reference statements)
1
12
0
1
Order By: Relevance
“…In this sample, the group mean PPO response (i.e., participants' best PPO from six sprints) was 723.1 § 180.3 watts. Our PPO data are similar to those reported for 17 year old boys performing a 30 s Wingate test against an identical resistive force of 0.075 kg kg ¡1 (707 § 114 watts) (Armstrong et al 2001), but lower than that reported on similar aged boys (1,409 § 197 watts) performing two 5 s cycling sprints (Dore et al 2006). Importantly, in Dore et al's study, the resistive force was 0.05 kg kg ¡1 .…”
Section: Discussionsupporting
confidence: 89%
“…In this sample, the group mean PPO response (i.e., participants' best PPO from six sprints) was 723.1 § 180.3 watts. Our PPO data are similar to those reported for 17 year old boys performing a 30 s Wingate test against an identical resistive force of 0.075 kg kg ¡1 (707 § 114 watts) (Armstrong et al 2001), but lower than that reported on similar aged boys (1,409 § 197 watts) performing two 5 s cycling sprints (Dore et al 2006). Importantly, in Dore et al's study, the resistive force was 0.05 kg kg ¡1 .…”
Section: Discussionsupporting
confidence: 89%
“…With the start of puberty, testosterone starts to increase in boys leading to an increase in skeletal muscle mass whereas fat mass increases in girls [19]. Due to the higher muscle mass strength is higher in boys compared to girls [20,21]. Additionally, aerobic capacity will become higher in boys compared to girls [22] and endurance performance will be higher in body than in girls [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…This is a little surprising with respect to the anaerobic energy used daily during infancy, childhood and adolescence. Indeed, during leisure-time activities or sport events, the child is spontaneously more attached to short-burst movements than to long-term activities (1,10).…”
mentioning
confidence: 99%